1999
DOI: 10.1021/om990301l
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer in Aminocyclopentadienyl Ruthenium Hydride Complexes

Abstract: A new ruthenium hydride complex of the aminocyclopentadienyl ligand (Cp-N)RuH(PPh3)2 (Cp-N = C5H4CH2CH2NMe2, 1) has been prepared and characterized by X-ray diffraction. Protonation of 1 with excess HPF6 leads to the dicationic derivative [(Cp-NH)RuH2(PPh3)2](PF6)2 (2), in which both the metal and the amino substituent have been protonated. Addition of 1 equiv of HBF4·Et2O to 1 leads to the complex [(Cp-N)Ru(PPh3)2](BF4) (3), containing a chelating amino cyclopentadienyl ligand after elimination of H2. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 40 publications
6
64
1
Order By: Relevance
“…[11] Then, the nucleophilic attack of a substrate (carboxylic acid or alcohol) to the hydride intermediate proceeds to give the corresponding silylated product. [10] The present [RuCl 2 A C H T U N G T R E N N U N G (p-cymene)] 2 -catalyzed dehydrosilylation with an optically active silane proceeded exclusively with inversion of stereochemistry at the chiral silicon center: the silylation of 4b (1.5 equivalents with respect to 2f) with R-(+)-methyl(1naphthyl)phenylsilane (92% ee) (2f) afforded R-(À)butoxymethyl(1-naphthyl)phenylsilane (5s) in 84% ee, for example [Eq. (6)].…”
Section: Resultsmentioning
confidence: 99%
“…[11] Then, the nucleophilic attack of a substrate (carboxylic acid or alcohol) to the hydride intermediate proceeds to give the corresponding silylated product. [10] The present [RuCl 2 A C H T U N G T R E N N U N G (p-cymene)] 2 -catalyzed dehydrosilylation with an optically active silane proceeded exclusively with inversion of stereochemistry at the chiral silicon center: the silylation of 4b (1.5 equivalents with respect to 2f) with R-(+)-methyl(1naphthyl)phenylsilane (92% ee) (2f) afforded R-(À)butoxymethyl(1-naphthyl)phenylsilane (5s) in 84% ee, for example [Eq. (6)].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on organometallic complexes have shown that pendant nitrogen bases play an important role in proton/hydride exchange reactions [21][22][23]. An understanding of proton transfer precess will be necessary for developing efficient hydrogen production/hydrogen oxidation catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…A greatly improved efficiency was obtained when a Ru catalyst was employed instead of Rh in the presence of the Pd co-catalyst. Among all the Ru catalysts investigated, [Ru 3 (CO) 12 ] was found to be the most effective counterpart when combined with [Pd 2 (dba) 3 ]·CHCl 3 . This combination afforded the ketone product in 83 % yield (5 mol % of each catalyst) in the presence of NaHCO 3 (1.5 equiv) at 135 8C (20 h).…”
mentioning
confidence: 99%
“…This result may rule out the possibility that the reaction of aldehyde 1 and iodoarenes proceeds by Rucatalyzed decarbonylation of 1 followed by Pd-catalyzed arylcarbonylation of iodobenzene. [9] In fact, there are several precedents for the [Ru 3 (CO) 12 ]-catalyzed orthometalation of nitrogen-containing heteroaromatic compounds to provide ortho-carbonylated adducts. [10] Aldehydes devoid of a coordinating group were not coupled with iodobenzene, which implies that activation of a formyl CÀH bond of 1 is coordination-directed [Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation